1995
DOI: 10.1515/jpme.1995.23.6.477
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related changes of carnitine and acylcarnitine concentrations of plasma and erythrocytes

Abstract: Total-, free-, and acylcarnitine concentrations were determined in whole blood, plasma, and red blood cells of 88 women during pregnancy. Already in the 12th week of gestation the mean whole blood carnitine level was significantly (p < 0.01) lower than those of the controls. From the 12th gestational week up to parturition there was a further significant (p < 0.01) decrease. This reduction of total carnitine in whole bloods was mainly caused by a significant (p < 0.01) decrease of free carnitine levels, since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 32 publications
8
32
0
6
Order By: Relevance
“…No mother or neonate had clinical manifestations of carnitine insufficiency. in the present study, as in several previous reports [6][7][8], have been attributed to transplacental transfer of FC to the fetus, which is not capable of producing carnitine. This is attributed to low activity of the enzyme γ-butyrobetaine hydroxylase being about 12% of adult values at birth [15,16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No mother or neonate had clinical manifestations of carnitine insufficiency. in the present study, as in several previous reports [6][7][8], have been attributed to transplacental transfer of FC to the fetus, which is not capable of producing carnitine. This is attributed to low activity of the enzyme γ-butyrobetaine hydroxylase being about 12% of adult values at birth [15,16].…”
Section: Discussionsupporting
confidence: 89%
“…Impairment of the carnitine shuttle may adversely affect FA oxidation leading to serious complications, especially during metabolic derangements, including liver dysfunction, skeletal myopathy, cardiomyopathy, and hypoketotic hypoglycemia [5]. Several studies in normal pregnancies have documented low plasma free carnitine (FC) levels approaching those observed in organic acidurias which, however, were not associated with clinical manifestations of carnitine insufficiency [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well described that plasma carnitine decreases during pregnancy from the 12th week of gestation to term and may reach concentrations half the normal in healthy nonpregnant women. The decrease in total carnitine is mainly caused by a decrease in free carnitine (Schoderbeck et al 1995) and is thought to be the consequence of a reduced rate of carnitine biosynthesis, possibly because of an inadequate iron status (Keller et al 2009) or because of a low availability of precursors for carnitine (Ringseis et al 2010). Interestingly, one study reported a complete normalization of plasma carnitine one month after delivery (Marzo et al 1994), and our finding of low-normal free carnitine 16 days after delivery may reflect a partial normalization to concentrations often seen in patients with MCADD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that FC and AC values are significantly higher in whole blood than in plasma (7,15,22 ) because of the significantly higher concentrations of long-chain ACs in the erythrocyte membrane. Plasma AC concentrations would most likely show a pattern of variation similar to the one observed in whole blood samples.…”
Section: Discussionmentioning
confidence: 99%